Three new species of the genus Kosalya Distant, 1906 (Hemiptera: Fulgoromorpha: Achilidae) from China - Long, Jian-Kun; Chen, Xiang-Sheng (Zootaxa, 2013)
Three new species of the planthopper genus Kosalya Distant, 1906 (Hemiptera: Fulgoromorpha: Achilidae: Plectoderini) are described and illustrated from China: K. unimaculata sp. nov., K. circumscripta sp. nov. and K. curvusanusa sp. nov.. The genus is redescribed, and includes male genitalia characters. A key to all species of the genus is given.